Phosphate Adsorption from Aqueous Solutions Using Eggshell and Sacha Inchi (Plukenetia volubilis) Mixture - López-Bermúdez, Nury Lorena; Rodríguez-Torres, Andrea Catalina; Otálvaro-Álvarez, Ángela María; Peña-Guzmán, Carlos Andrés (Civil Engineering Journal, 2025)
The use of bioadsorbents for the removal of pollutants is being increasingly investigated worldwide due to their high efficiency and the potential use of various natural sources. The present study introduces a novel approach for phosphate adsorption using sacha inchi cuticle and eggshell mixture. These materials were pyrolyzed (400°C for 20 min) and mixed in a 1:10 (eggshell:cuticle) ratio. An adsorption study was carried out using synthetic phosphate solution concentrations of 0–300 mg/L and adsorbent masses of 0.1–1 g/100 mL. The temperature, pH and stirring were kept constant (25°C, pH:5 and 150 rpm) during the tests. The phosphate adsorption capacity increased as higher phosphate concentrations were used, reaching a maximum of 300 mg/L. However, differences in removal were observed when varying the amount of adsorbent used, reaching equilibrium in approximately 1 h, with a percentage of phosphate removal between 31 and 41%. The adsorption process followed a Freundlich isotherm with a correlation coefficient of 0.97, suggesting a multilayer adsorption process. According to the SEM-EDX results confirmed a high concentration of carbon and oxygen in the sacha inchi cuticle, in that sense, this by-product could be evaluated for the removal of other contaminants from water.